Implementation of artificial intelligence in the form of canva in the learning process in the digital era - Rina Andarwati; Galih Adi Widodo; Eko Darmanto (Sean Institute, 2024)
This research aims to analyze the application of artificial intelligence in the form of Canva in the learning process in the digital era. The type of research used is qualitative research with a descriptive approach. The research was conducted at an elementary school in Pati district. Data collection techniques carried out by researchers used interviews, observation and documentation studies with interview guide instruments, observation sheets and related documents. Data analysis carried out in this research includes data reduction, data presentation and drawing conclusions. The results of the research obtained data show that the use of AI technology in the form of Canva can provide significant benefits for teachers when they face the challenges of the digital era. By using artificial intelligence technology, teachers can manage data more effectively, provide personalized learning, and provide effective feedback to students. However, it is important to remember the limitations and challenges associated with the use of artificial intelligence technology in education